PENGARUH SENAM DIABETES TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 DI PAGUYUBAN DIABETES PUSKESMAS II DENPASAR BARAT - Dewi, Indra Suwari (Coping: Community of Publishing in Nursing, 2014)
Type 2 diabetes is a disease caused by hyperglycemia cell insensitivity to insulin  which  is  a  type  of  diabetes  that  affects  most  people.  Physical  activity  is best  done  one  exercise  diabetes.  This  study  aimed  to  determine  the  effect  of exercise on blood sugar levels of diabetes in patients with type 2 diabetes. This study  is  a  quasi  experimental  study  (pretest-postest  control  group  design).  The sample consisted of 20 people chosen by purposive sampling, were divided into two  groups:  treatment  group  and  control  group.  The  data  was  collected  using primary data on blood sugar levels of patients with type 2 diabetes. The results of 10 samples at post-test treatment group showed the lowest blood sugar levels of 160 mg / dl and the highest blood sugar levels 290 mg / dl. Whereas in the control group at post-test obtained a description of the lowest blood sugar was 190 mg / dl and the highest blood sugar levels were 310 mg / dl. Based on independent t-test analysis it can  be concluded that there is a gymnastic effect of diabetes on blood sugar  levels  in  diabetic  patients  type  2  diabetes  in  Diabetes  Health  Centre  of Puskesmas II Denpasar Barat  (p value: 0.000 <?: 0,05). Based on these studies is recommended  to  patients  with  type  2  diabetes  to  increase  the  frequency  of diabetes gymnastics.
Keywords: Type 2 diabetes; gymnastic of diabetes; blood sugar